Chromosomal engineering of inducible isopropanol- butanol-ethanol production in Clostridium acetobutylicum - Omorotionmwan, Bunmi B.; Wang, Hengzheng; Baker, Jonathan P.; Gizynski, Krzysztof; Yoo, Minyeong; Akaluka, Cynthia; Zhang, Ying; Minton, Nigel P. (Frontiers in Bioengineering and Biotechnology, 2023)
The use of environmentally damaging petrochemical feedstocks can be displaced by fermentation processes based on engineered microbial chassis that recycle biomass-derived carbon into chemicals and fuels. The stable retention of introduced genes, designed to extend product range and/or increase productivity, is essential. Accordingly, we have created multiply marked auxotrophic strains of Clostridium acetobutylicum that provide distinct loci (pyrE, argH, purD, pheA) at which heterologous genes can be rapidly integrated using allele-coupled exchange (ACE). For each locus, ACE-mediated insertion is conveniently selected on the basis of the restoration of prototrophy on minimal media. The Clostridioides difficile gene (tcdR) encoding an orthogonal sigma factor (TcdR) was integrated at the pyrE locus under the control of the lactose-inducible, bgaR::PbgaL promoter to allow the simultaneous control of genes/operons inserted at other disparate loci (purD and pheA) that had been placed under the control of the PtcdB promoter. In control experiments, dose-dependent expression of a catP reporter gene was observed with increasing lactose concentration. At the highest doses tested (10 mM) the level of expression was over 10-fold higher than if catP was placed directly under the control of bgaR::PbgaL and over 2-fold greater than achieved using the strong Pfdx promoter of the Clostridium sporogenes ferredoxin gene. The utility of the system was demonstrated in the production of isopropanol by the C. acetobutylicum strain carrying an integrated copy of tcdR following the insertion of a synthetic acetone operon (ctfA/B, adc) at the purD locus and a gene (sadh) encoding a secondary dehydrogenase at pheA. Lactose induction (10 mM) resulted in the production of 4.4 g/L isopropanol and 19.8 g/L Isopropanol-Butanol-Ethanol mixture.